Accelerating Agricultural Growth—Is Irrigation Institutional Reform Necessary? (Distinguishedl Lecture) (The Pakistan Development Review, 1996)
The right to the flow of income from water is vigorously pursued, protected, and fought over in any arid part of the world. Pakistan is of course no exception. Reform of irrigation institutions necessarily changes the rights to water, whether it be those of farmers, government, or government functionaries. Those perceived rights may be explicit and broadly accepted, or simply takings that are not even considered legitimate. Nevertheless they will be fought over. Pakistan has a long history of proposals for irrigation reform, little or none being implemented, except as isolated pilot projects. Thus, to propose major changes in irrigation institutions must be clearly shown to have major benefits to justify the hard battles that must be fought and the goodwill of those who might win those battles for reform. Proponents of irrigation institution reform have always argued the necessity of the reforms and the large gains to be achieved. Perhaps, however, those arguments have not been convincing. This paper will briefly outline the failed attempts at irrigation reform to provide an element of reality to the discussion. It will then proceed to make the case of the urgency of reform in a somewhat different manner to the past. Finally, current major reform proposals will be presented. This paper approaches justification of irrigation reform by focusing on the agricultural growth rate. It does so because that is the critical variable influencing poverty rates and is a significant determinant of over-all economic growth rates. The paper decomposes growth rates and suggests a residual effect of deterioration of the irrigation system that is large and calls for policy and institutional reform. The data are notional, suggesting the usefulness of the approach and paves the way for more detailed empirical analysis and enquiry for the future.